2014
DOI: 10.3389/fonc.2014.00116
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin is a Hypoxia-Active Anti-Cancer Drug in Colorectal Carcinoma Cells

Abstract: Tumor hypoxia is one main biological factor that drives resistance to chemotherapy and radiotherapy. To develop a novel strategy for overcoming hypoxia-induced therapy resistance, we examined the anti-neoplastic activity of the reactive oxygen donor dihydroartemisinin (DHA) in human colon cancer cell lines in normoxia and severe hypoxia. In addition, we analyzed the involvement of the intrinsic apoptosis pathway for DHA-mediated cytotoxicity in HCT116 cells in short-term and long-term in vitro assays. When app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…6a-c) support the notion that Mcl-1 preferentially restricts the activation of Bak but not Bax [46,56]. It was demonstrated that overexpression of Mcl-1 in HCC cells enhanced cell resistance to apoptosis [57], and DHA-induced apoptosis was accompanied by a downregulation of Mcl-1 in leukemia cells [55] and in colon cancer cells [33]. Handrick et al proved that the rapid decline of Mcl-1 was associated with Bak activation during DHA-induced apoptosis in Jurkat cells [25].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…6a-c) support the notion that Mcl-1 preferentially restricts the activation of Bak but not Bax [46,56]. It was demonstrated that overexpression of Mcl-1 in HCC cells enhanced cell resistance to apoptosis [57], and DHA-induced apoptosis was accompanied by a downregulation of Mcl-1 in leukemia cells [55] and in colon cancer cells [33]. Handrick et al proved that the rapid decline of Mcl-1 was associated with Bak activation during DHA-induced apoptosis in Jurkat cells [25].…”
Section: Discussionmentioning
confidence: 62%
“…Some publications also showed that DHAinduced Bax-mediated apoptosis was accompanied by a decline of Bcl-2 expression in HCC cells [15,26], pancreatic cancer cells [18] and ovarian cancer cells [19,54]. However, other reports demonstrated that DHA did not influence the expression of Bcl-2/Bcl-xl in leukemia cells [25,55], colon cancer cells [33] and HCC cells (Bcl-xl) [27]. These discrepancies may stem from the different pathways through which DHA induces apoptosis in distinct cancer cells that possess their own cellular systems to response to apoptotic stimuli [25].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Dihydroartemisinin (DHA), the major active metabolite of artemisinin, has been found to inhibit the growth of cancer cells in a variety of cancers (12)(13)(14)(15). Xie et al (16) reported that the concentration of DHA was two-fold higher in the brain than in the plasma, which indicates that DHA is able to penetrate the brain-blood barrier.…”
Section: Introductionmentioning
confidence: 99%